Circulation and translation of political thought: exchanges, production and hegemony (Res Publica. Revista de Historia de las Ideas Políticas, 2023)
This essay aims to contribute to the methodological debate of intellectual history in favor of a transactional approach. In order to do so, it will present the circulation and translation of political and social ideas, from different perspectives, since the preliminary historiographical approximations of the beginning of the 20th century, in particular the Italian one, based on the analogy of international commerce to think the process of diffusion and exchange of ideas, to the more recent developments made by the Cambridge School and the History of Concepts, centered on the potential of the translation metaphor to think about the productive character of the process of translating ideas between different geographical and temporal contexts.